Perspectives of Policymakers on the Introduction and Scale-Up of HIV Self-Testing and Implication for National HIV Programming in Ghana - Nagai, Henry; Tagoe, Henry; Tun, Waimar; Adiibokah, Edward; Ankomah, Augustine; Rahman, Yussif Ahmed Abdul; Addo, Stephen Ayisi; Atuahene, Stephen Kyeremeh; Essandoh, Emmanuel; Kowalski, Mark (Frontiers in Public Health, 2021)
Background: HIV self-testing (HIVST) has the potential to greatly increase HIV testing uptake, particularly among key populations (KPs) at higher risk for HIV. Studies have shown high acceptability and feasibility of HIVST among various target populations globally. However, less is known about the perspectives of policymakers, who are critical to the success of HIVST implementation. Their views on barriers to the introduction and scale-up of self-testing are critical to understand in order for HIVST to become part of the national HIV guidelines. We sought to understand policymakers' perspectives of challenges and facilitators to the introduction of HIVST at the client and structural levels. Method: Key informant interviews (KIIs) were conducted with national and regional level policymakers involved in the HIV response. Twenty policymakers were purposively selected from Greater Accra (capital) and Brong-Ahafo (outlying) regions. Qualitative content analysis was used to arrive at the results after the verbatim transcripts were coded. Results: Client-level challenges included lack of pre-test counseling, the need for confirmatory testing if reactive, potential for poor linkage to care and treatment, and client-level facilitator from policy makers' perspectives included increase testing modality that would increase testing uptake. Structural-level challenges mentioned by policymakers were lack of a national policy and implementation guidelines on HIVST, cost of HIVST kits, supply chain management of HIVST commodities, data monitoring and reporting of positive cases. The structural-level appeal of HIVST to policymakers were the reduced burden on health system and HIVST's contribution to achieving testing targets. Despite the challenges mentioned, policymakers unanimously favored and called for the introduction of HIVST in Ghana. Conclusions: Findings indicate that a non-conventional HIV testing strategy such as HIVST is highly acceptable to policymakers. However, successful introduction of HIVST hinges on having national guidelines in place and stakeholder consultations to address various individual and structural -level implementation issues.